On solving split best proximity point and equilibrium problems in Hilbert spaces - Jukrapong Tiammee (2020)
© 2019, SINUS Association. All rights reserved. In this paper, we introduce a split best proximity point and equilibrium problem, and find a solution of the best proximity point problem such that its image under a given bounded linear operator is a solution of the equilibrium problem. We construct an iterative algorithm to solve such problem in real Hilbert spaces and obtain a weak convergence theorem. Finally, we also give an example to illustrate our result.